Kayaking A Beginner's Guide - Nigel Foster October 17, 1952 (Arundel, West Sussex Fernhurst Books, 1999)
Kayaking is a tremendously wide-ranging sport. You can go for a leisurely paddle on your local pond, travel down a river of experience the thrills of white water. It is truly a sport for life. This lavishly-illustrated, clearly written guide will have you out on the water fast - and in safety.